Reviews Fall 2018. Issue 1 (18th December 2018) - Raynsford, Anthony; Figueira, Jorge; Erten, Erdem; Christensen, Peter H.; Watson, Victoria
Abstract : Raynsford, A. Review of: Wolfgang Sonne, Urbanity and Density in 20th Century Urban Design, Berlin: DOM Publishers, 2017. Figueira, J. Review of: Léa-Catherine Szacka, Exhibiting the Postmodern: The 1980 Venice Architecture Biennale, Venezia: Marsilio Editori, 2016. Erten, E. Review of: Meltem O. Gürel, eds., Mid-Century Modernism in Turkey (Architecture Across Cultures in the 1950s and 1960s), Routledge: London and New York, 2016. Christensen, P. Review of: Aldo Rossi: The Architecture and Art of the Analogous City, Princeton University School of Architecture, February 5 to March 30, 2018. Watson, V. Review of: Mies van der Rohe + James Stirling: Circling the Square, The Architecture Gallery, RIBA, March 8 to June 25, 2017.